Medical students' attitudes towards abortion: a UK study. Issue 11 (30th October 2008) - Gleeson, R; Forde, E; Bates, E; Powell, S; Eadon-Jones, E; Draper, H
Abstract : Background: There is little research into medical students' or doctors' attitudes to abortion, yet knowing this is important, as policy makers should be aware of the views held by professionals directly involved in abortion provision and changing views may have practical implications for the provision of abortion in the future. Methods: We surveyed 300 medical students about their views on abortion, their beliefs about the status of the fetus and the rights of the mother, their attitude towards UK law and their willingness to be involved in abortion provision as qualified doctors. Results: 62% of medical students were pro-choice, 33% pro-life and 7% undecided. Students' views correlated with gender, year of study and holding a religious belief. Their beliefs about abortion, the status of the fetus and the rights of women significantly correlated with their attitudes towards the UK law and their willingness to be involved in abortion provision. Students' willingness to be involved in abortion provision was related to their views on abortion, the extent of participation required, the circumstances of the pregnancy and the stage of pregnancy. Conclusions: The percentage of pro-choice students was lower than that found in research on general practitioners' attitudes to abortion. It is unclear whether this is because students become more pro-choice as they progress through their medical career or because there is genuinely a change in attitudes to abortion.